Hydrothermal Carbonization of Agro-industrial By-products for the Production of Valuable Chemicals - Fabrizio Di Caprio; Flavia Marzulli; Pietro Altimari; Marianna Villano; Francesca Pagnanelli (Chemical Engineering Transactions)
The development of a sustainable bioeconomy requires the application of effective technological solutions to recycle organic molecules into valuable products. Hydrothermal treatments are thermochemical processes that can be employed to depolymerize biomass into small organic molecules suitable for new applications. Most of the research on hydrothermal processes has focused on the stabilization of the organic compounds, producing a carbonaceous hydrochar material, while less attention has been given to the extraction of valuable organic molecules. In this study, we investigated the effects of temperature (160 and 190 °C) and reaction time (15 and 60 min) on the hydrothermal treatment of two different biomasses: orange peels and barley straw. Both the solid hydrochar and the aqueous extracts were chemically characterized. Specifically, the aqueous extracts were analyzed for their content of released organic molecules and were tested by respirometry to assess their potential as substrates for microbial fermentations. Results showed that lower temperatures and shorter reaction times led to the release of higher concentrations of soluble organic molecules, reaching a COD (Chemical Oxygen Demand) value up to 161 g L?¹, phenols up to 5.5 g L?¹, and carbohydrates up to 47 g L?¹. Orange peels released the highest concentrations of organic molecules in the process water, but this water was poorly biodegradable by mixed microbial cultures (21% biodegradable COD). The process water from the hydrothermal carbonization of barley straw at 190 °C for 15 minutes was the most biodegradable stream (34% biodegradable COD) between those investigated and was the most suitable for microbial fermentation, due to its higher acetic acid content. This stream did not cause short-term inhibition of microbial cultures. These preliminary results are promising, but further work is needed to optimize the application of these streams for the production of specific value-added pro